Economic-Environmental and Multi-Criteria Optimization for Predicting Alkaline Ratios in Waste Cement Concrete-Based Geopolymer Using Central Composite Design - Mohammed Rihan Maaze; Sourav Kumar Das; Nikhil Garg; Sandeep Shrivastava (International Journal of Concrete Structures and Materials)
Abstract India, as the world's second-largest cement producer, faces significant environmental challenges due to high carbon emissions from cement production. This study investigates the potential of using waste cement concrete (WCC) powder as a sustainable precursor in geopolymer concrete, aiming to advance sustainable development and effective waste management. Utilizing a central composite design (CCD) approach, the research optimizes molarity (M) and alkaline mix (AM) ratios to enhance the material's properties. Findings reveal that heat curing increases the 28-day compressive strength by 15–20% compared to room-temperature curing. Moreover, environmental impact assessments indicate a 15% reduction in Global Warming Potential (GWP) and a 12% reduction in Acidification Potential (AP), despite a 30% higher fossil fuel (FF) impact due to alkali use compared to traditional Portland cement mortar. Multi-response desirability analysis identifies the optimal molarity (10) and alkaline mix ratio (2.5) for achieving balanced performance across compressive strength, water absorption, shrinkage, tensile bond strength, and GWP. The confirmation experiments validate these predictive models, showing close alignment between predicted and observed values, ensuring the reliability and accuracy of the optimization approach. The study concludes that geopolymer mortars, particularly those cured at 60 °C with a 10 M NaOH solution and the optimal alkaline ratio, offer an environmentally friendly and mechanically superior alternative to conventional cement mortars. This approach supports sustainability by reducing environmental impact, promoting effective waste management, and contributing to sustainable development in the construction industry.